Investigating the Motions Behavior of a Ferry in Waves Caused by Damaged Conditions - Suandar Baso (International Journal of Marine Engineering Innovation and Research, 2021)
A progressive flooding-ingress of water to a compartment of a damaged ship affects the motions of a ship. In this present study, the behavior of the motion of a ferry caused by damaged conditions in waves was investigated through the experimental work. The leakage of compartments was made into several scenarios including one, two, and three damaged compartments, and the damaged ship model was simulated in heading and beam waves. The research results show the one damaged compartment on the engine room (ER) affected extreme stern trim as well as Void No.1 affected extreme bow trim. The two damaged compartments on the water ballast tank (WBT) No.2 and Steering gear room (SGR) resulted in extreme stern trim as well as WBT No.1 and Void No.1 affected extreme bow trim. The heave, pitch, and roll responses on the damaged Void No.1 are higher comparing with the damaged ER. Also, the heave, pitch, and roll responses on damaged SGR and WTB No.2 are higher than Void No.1 and WBT No.1. The peak resonances of heave RAO on bow trim affect higher magnitude than on stern trim. Pitch or roll RAO caused by the increased bow trim or stern trim in head and beam waves has a small magnitude within the response.